Persuasion methods in advertising posters: A semiological study of an advertising poster for a cosmetics company as a model - Seghiri, Racha Wissal; Mefaredj, Djamel (Journal of Human Sciences, 2023)
Our study focused on the subject of "Methods of persuasion in advertising posters - a semiological study of an advertising poster for the Lancôme cosmetics company as an example -" where we talked about the nature of the persuasive process in the field of communication, then we specialized in the advertising poster and its relationship to persuasion and its methods. The study aimed to reveal the methods of persuasion employed by the "Lancôme" company in designing its advertising posters for La vie est belle perfume, by applying the method of semiological analysis to the selected sample, which was chosen by the intentional sampling method. We analyzed it through the tools of observation and semiological analysis according to The methodology developed by "Roland Gervio", to reach a set of results according to which the "Lancôme" company uses many persuasive methods, but in varying proportions.